The Correlation of Gamma-Glutamyl Transferase (γ-GT), Glutathione Peroxidase (GPx) and Total Antioxidant Status (TAS) with Inflammatory Marker in Individuals with Metabolic Syndrome - Susana Gunawan; Anwar Santoso; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: γ-GT is known as a primary enzyme that constituent extracellular glutathione catabolism. Various researches have proven that an increase in γ-GT concentration is related to oxidative stress and to components of metabolic syndrome. With individuals having metabolic syndrome as research subjects, our objective is to find the correlation of γ-GT, GPx and SAT.METHODS: This was a cross sectional study done on 36 subjects with metabolic syndrome who met the IDF 2005 criteria. Statistical analysis was carried out using SPSS for Windows ver.11.5 with a significance level of p<0.05. The correlation among biomarkers were assessed using Spearman’s Rho test.RESULTS: γ-GT concentration was correlated negatively with GPx concentration (r=-0.411, p=0.014), but correlated positively with hs-CRP concentration (r=0.385, p=0.022). The increase of γ-GT concentration had a potential risk 8.5 times higher than the increase of hs-CRP concentration, which proved to be more dominant in comparison to its risk to γ-GT/GPx or γ-GT/SAT ratios (p<0.05).CONCLUSIONS: An increase in γ-GT concentration characterizes signs of oxidative stress syndrome and of inflammation in individuals with metabolic syndrome.KEYWORDS: γ-GT, GPx, SAT, inflammation, metabolic syndrome